2011
DOI: 10.1118/1.3604151
|View full text |Cite
|
Sign up to set email alerts
|

The management of tumor motions in the stereotactic irradiation to lung cancer under the use of Abches to control active breathing

Abstract: Respiratory control with high accuracy and reproducibility is required for high-precision radiotherapy of inoperable nonsmall-cell lung cancer and was achieved using Abches in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 22 publications
1
17
0
1
Order By: Relevance
“…A BlueBAG system (Medical Intelligence, Munich, Germany) was used to immobilize patients. To maintain tumor positions during irradiation, patients were instructed in the self-controlled breath-hold technique using an Abches (APEX Medical, Tokyo, Japan) respiratory monitoring system [20]. This system was used during CT scanning for treatment planning and irradiation, and breath was held at inspiration or expiration.…”
Section: Methodsmentioning
confidence: 99%
“…A BlueBAG system (Medical Intelligence, Munich, Germany) was used to immobilize patients. To maintain tumor positions during irradiation, patients were instructed in the self-controlled breath-hold technique using an Abches (APEX Medical, Tokyo, Japan) respiratory monitoring system [20]. This system was used during CT scanning for treatment planning and irradiation, and breath was held at inspiration or expiration.…”
Section: Methodsmentioning
confidence: 99%
“…This device has been extensively used, particularly in Asia, to treat multiple sites, including lung, liver, and breast cancer. In a study including 32 NSCLC, Tarohda, et al concluded that the Abches device could be effectively used to obtain appropriate reproducibility of tumor position during lung SABR under breath holding conditions [5]. Lee, et al observed that Abches could be used to treat left-sided breast cancer in a deep inspiration breath-hold setting with potential dose reduction to the heart [7].…”
Section: Figure 3: Ct Images and Treatment Isodoses Of A Marginal Bhmentioning
confidence: 99%
“…The benefits of Abches monitoring device to ensure reproducible BH radiotherapy treatment have been established in several previous studies [1,[4][5][6][7]. This device has been extensively used, particularly in Asia, to treat multiple sites, including lung, liver, and breast cancer.…”
Section: Figure 3: Ct Images and Treatment Isodoses Of A Marginal Bhmentioning
confidence: 99%
See 1 more Smart Citation
“…6, 7) 적 향상을 저하 시키는 원인이 되기도 하였다, [13] 방사선이 정상 간에 노출이 되었을 경우 방사선으 로 혈관이 막히면서 간이 손상된다는 연구결과가 보 고 되었으며 [14] , 방사선으로 인한 간질환은 방사선 치 료 후 보통 4-8주 후에 발생하지만 문헌에 따르면 방 사선 치료 후 이르면 2주 후부터 늦으면 7개월 후까지 도 발생하는 것으로 보고되고 있다. …”
unclassified